To Bother or Not to Bother? Media Relationship Development Strategies of Agricultural Communication Professionals - Amanda Ruth-McSwain; Ricky Telg (Journal of Applied Communications, 2008)
As the media relations function becomes increasingly important for organizational visibility, accountability, and ultimately survival, it is imperative that effective media communication strategies be employed to develop mutually benef icial relationships with the news media. Based on the conceptual framework of dialogic communication, this study is an investigation of the media relations practices and strategies of agricultural communication professionals in their role as the sources of agricultural information for the news media. Findings from the study indicate differing media relations strategies and relevant themes; however, a notable theme that materialized was the perception of having mutually beneficial relationships with the media that lack regular dialogue. An additional finding of interest was the change in media relations strategy from a passive approach to an active approach; participants suggested that their approaches to working with the media tended to be reactive in nature, but indicated that they have recently developed proactive initiatives in establishing media contact. Overall, the study identified effective media relations practices and provided insight into areas that could benefit from enhanced media relations strategies for agricultural communication academicians and practitioners.
Keywords: Media Relationship Development Strategies; news media; Strategies; enhanced media; conceptual framework